Fostering Students' Environmental Awareness through the Family Medicinal Plants (Toga) Program - Nurul Maulida (Lembaga Bale Literasi, 2025)
Growing and caring for medicinal plants is an essential skill that is essential for improving students' critical, creative, and communicative thinking abilities in elementary school. However, the problem of students who are not interested in the environment and medicinal plants still needs to be addressed. The purpose of the Community Service (PKM) activity is to increase the knowledge and awareness of SDN 2 Kelayu Utara students about medicinal plants by creating a medicinal garden. This article discusses the results. Qualitative descriptive methods are used in this study. The stages of the activity consist of initial observation of the condition of the school environment, arrangement and procurement of interesting medicinal plants, selection of types of medicinal plants that are suitable for the age of students, and the application of the habit of planting and caring for plants every day. After the data was collected through activity documentation, informal interviews, and observations, changes in students' behavior and awareness of medicinal plants were examined through descriptive analysis. The results of the activity showed that the students' enthusiasm for growing and caring for medicinal plants increased, which was demonstrated by the increased ability to understand the benefits of medicinal plants, and the habit of sharing knowledge about medicinal plants. In addition, this activity creates a more relaxed, fun, and environment-based learning environment. As a result, the development of medicinal plants through PKM activities has proven to be effective in building a culture of caring for the environment and fostering awareness among elementary school students about the importance of medicinal plants consistently.